PERAN PENGAJAR DALAM WACANA KELAS PEMBELAJARAN BIPA DARING - Winasti Rahma Diani; Asri Wijayanti; Meilina Meilina (Universitas Muhammadiyah Surakarta, 2022)
The Covid-19 pandemic has encouraged teachers and students to adapt to online learning synchronously, asynchronously, or via hybrid. The synchronous online learning is widely chosen for foreign language learning, such as BIPA (Indonesian Language for Foreign Learner). BIPA teachers and students can interact as a classical class through synchronous online learning. Therefore, this study aims at finding the role of the teacher in the classroom discourse of online BIPA learning. The observations were conducted in the classroom of online BIPA learning using Google Meet application as a learning media. From the observations, it was found that the roles of teachers and students were not balanced since the teacher had a very dominant role in the classroom discourse. The dominance of the teacher's role can be seen from the teacher's actions in controlling interaction, modifying speech, eliciting, and repair. As a result, the teacher's role affects the interaction patterns, students' opportunities to use the target language, students' understanding, and students' ability to solve problems.